How Does AI Support Mass Casualty Incident Response? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Mass casualty incidents (MCIs) represent a formidable challenge to any healthcare system, creating a sudden surge of patients that can quickly overwhelm avai...
Keywords: AI in Emergency Medicine; Support; Casualty; Incident; Artificial Intelligence; Machine Learning; Healthcare